A Volume Preserving Map from Cube to Octahedron (Global Journal of Science Frontier Research, 2018)
Using simple geometric reasoning we deduce a volume preserving map from the cube to the octahedron.
Keywords: geometric reasoning; octahedron; volume preserving map